Securitology - The Concept of Safety - Korzeniowski, Leszek (Communications - Scientific letters of the University of Zilina, 2005)
In the article the author presents his own definition of the category of safety, emphasizing both: objective and subjective aspects of this idea. The author, on the basis of available publications, carries out the presentation of securitology as the scientific discipline as well as categories studied within that science, like: security, needs value and sense of safety, risk, danger, personality of a manager, etc. In the article are included proposals of a security model covering objective dangers and the sense of safety.